Sustained drug release using cobalt oxide nanowires for the preparation of polymer-free drug-eluting stents - Bedair, Tarek M.; Min, Il Jae; Park, Wooram; Joung, Yoon Ki; Han, Dong Keun (SAGE PUBLICATIONS LTD, 2018)
Polymer-based drug-eluting stents (DESs) represented attractive application for the treatment of cardiovascular diseases; however, polymer coating has caused serious adverse responses to tissues such as chronic inflammation due to acidic by-products. Therefore, polymer-free DESs have recently emerged as promising candidates for the treatment; however, burst release of drug(s) from the surface limited its applications. In this study, we focused on delivery of therapeutic drug from polymer-free (or -less) DESs through surface modification using cobalt oxide nanowires (Co3O4 NWs) to improve and control the drug release. The results demonstrated that Co3O4 NWs could be simply fabricated on cobalt-chromium substrate by ammonia-evaporation-induced method. The Co3O4 NWs were uniformly arrayed with diameters of 50-100 nm and lengths of 10 mu m. It was found that Co3O4 NWs were comparatively stable without any delamination or change of the morphology under in vitro long-term stability using circulating system. Sirolimus was used as a model drug for studying in vitro release behavior under physiological conditions. The sirolimus release behavior from flat cobalt-chromium showed an initial burst (over 90%) after one day. On the other hand, Co3O4 NWs presented a sustained sirolimus release rate for up to seven days. Similarly, the polymer-less specimens on Co3O4 NWs substrates sustained sirolimus release for a longer-period of time when compared to flat Co-Cr substrates. In summary, the current approach of using Co3O4 NWs-based substrates might have a great potential to sustain drug release for drug-eluting implants and medical devices including stents.
Keywords: CHROMIUM ALLOY SURFACES; INTERFACIAL ADHESION; PACLITAXEL DELIVERY; METAL-SURFACE; SIROLIMUS; IMPLANTATION; RESTENOSIS; NANOCOMPOSITE; PROLIFERATION; HYPERPLASIA